Investigations of Crucial Factors for the Non-Covalent Functionalization of Black Phosphorus (BP) using Perylene Diimide Derivatives for the Passivation of BP Nanosheets - Eisenkolb, Jasmin; Lloret, Vicent; Zink-Lorre, Nathalie; Pla, Sara; Abellán, Gonzalo; Sastre-Santos, Ángela; Hauke, Frank; Fernández-Lázaro, Fernando; Hirsch, Andreas (Chemistry - A European Journal, 2024)
The non-covalent functionalization of black phosphorus (BP) was studied with a scope of ten tailor-made perylene diimides (PDIs). A combination of UV/Vis-, fluorescence-, as well as Raman spectroscopy and atomic force microscopy was used to investigate the structural factors, which contribute to a pronounced PDI-BP interaction and thus support the protection of BP nanosheets against oxidative degradation. We were able to show, that water-soluble, amphiphilic PDIs with highly charged head groups can be used for the non-covalent functionalization of BP in aqueous media. Here, based on the hydrophobic effect, an efficient adsorption of the respective PDI molecules takes place and leads to the formation of a passivating film, yielding a considerable stabilization of the BP flakes under ambient conditions exceeding 30 days.
CRIS-Team Scopus Importer:2024-11-08
Keywords: Non-covalent functionalization; Passivation; Perylene diimides; Phosphorus; Supramolecular chemistry

Moiré Lattice of Twisted Bilayer Graphene as Template for Non-Covalent Functionalization - Dierke, Tobias; Wolff, Stefan; Gillen, Roland; Eisenkolb, Jasmin; Nagel, Tamara; Maier, Sabine; Kivala, Milan; Hauke, Frank; Hirsch, Andreas; Maultzsch, Janina (Angewandte Chemie International Edition, 2025)
Keywords: 2D materials; Graphene; Raman spectroscopy; Density functional calculations; Functionalization

Simultaneous Inside and Outside Functionalization of Single-Walled Carbon Nanotubes - Kraus, Jan; Meingast, Laura; Hald, Janina; Beil, Sebastian B.; Biskupek, Johannes; Ritterhoff, Christian; Gsänger, Sebastian; Eisenkolb, Jasmin; Meyer, Bernd; Kaiser, Ute; Maultzsch, Janina; von Delius, Max (Angewandte Chemie International Edition, 2024)
Functionalizing single-walled carbon nanotubes (SWCNTs) in a robust way that does not affect the sp2 carbon framework is a considerable research challenge. Here we describe how triiodide salts of positively charged macrocycles can be used not only to functionalize SWCNTs from the outside, but simultaneously from the inside. We employed disulfide exchange in aqueous solvent to maximize the solvophobic effect and therefore achieve a high degree of macrocycle immobilization. Characterization by Raman spectroscopy, EDX-STEM and HR-TEM clearly showed that serendipitously this wet-chemical functionalization procedure also led to the encapsulation of polyiodide chains inside the nanotubes. The resulting three-shell composite materials are redox-active and experience an intriguing interplay of electrostatic, solvophobic and mechanical effects that could be of interest for applications in energy storage.
CRIS-Team Scopus Importer:2024-04-19
Keywords: disulfide exchange; HRTEM; polyiodide; Raman spectroscopy; SWCNT